Curable composition, cured layer using the same, color filter including the cured layer, and display device including the color filter
Patent Information
- Application Number
- CN202580021186.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-09
- Filing Date
- 2025-02-13
- Publication Date
- 2026-10-20
AI Technical Summary
为了改善无溶剂可固化组成物的光学特性,通常使用增加无机材料含量的方法,但随着无机材料含量的增加,反射率增加且组成物的黏度增加,使得喷墨变得困难
[0072]在含量子点的可固化组成物的情况下,大多数尝试都是通过增加外部量子效率来改善光学特性。然而,本发明涉及一种含量子点的可固化组成物,其能够通过增加接近530纳米的光透光率而非外部量子效率来改善正面亮度,且通过使用根据实施例的含量子点的可固化组成物,可在最小化量子点的光效率降低的同时显著增加正面亮度。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This disclosure relates to a curable composition, a curable layer using the composition, a color filter including the curable layer, and a display device including the curable layer. Background Technology
[0002] In the case of general quantum dots, the solvent in which the quantum dots are dispersed is limited due to their hydrophobic surface properties, and therefore it is difficult to introduce them into polar systems (such as adhesives or curable monomers).
[0003] For example, even with active research into quantum dot ink compositions, the polarity is relatively low in the initial steps, and they can be dispersed in solvents used in highly hydrophobic curable compositions. Therefore, since it is difficult to include 20% by weight or more of quantum dots in the total composition, it is impossible to improve the light efficiency of the ink beyond a certain level. Even if additional quantum dots are added and dispersed to improve light efficiency, the viscosity exceeds the range suitable for inkjet printing, and therefore processability may not be satisfied.
[0004] To achieve a viscosity range suitable for inkjet printing, reducing the ink solids content by dissolving 50% or more of the solvent by weight of the total composition provides a slightly satisfactory result in terms of viscosity. However, while the viscosity may be considered satisfactory, issues such as nozzle drying and clogging due to solvent evaporation during inkjet printing, and the reduction in single-layer thickness over time after inkjet printing, can worsen, and thickness deviations after curing are difficult to control. Therefore, it is difficult to apply this method to practical processes.
[0005] Therefore, solvent-free quantum dot inks that do not contain solvents are the most ideal form for practical applications, and current technologies for applying quantum dots themselves to solvent-based compositions are currently limited to some extent.
[0006] Solvent-free curable compositions (quantum dot ink compositions) contain excessive polymerizable compounds, leading to nozzle drying, nozzle clogging, and emission failures due to volatility, as well as reduced single-film thickness due to the evaporation of the ink composition ejected into the patterned septum pixels. Therefore, efforts are underway to improve the optical properties of solvent-free curable compositions from various angles. Increasing the inorganic material content is a common method to improve the optical properties of solvent-free curable compositions; however, as the inorganic material content increases, reflectivity and viscosity of the composition increase, making inkjet printing difficult. Summary of the Invention
[0007] Technical issues
[0008] One embodiment provides a curable composition that can improve the transmittance of a curable layer containing green quantum dots, thereby maintaining the luminous efficiency of the quantum dots and increasing the transmittance of the green light source to the curable layer, thereby ultimately increasing front luminance.
[0009] Another embodiment provides a cured layer manufactured using the said curable composition.
[0010] Another embodiment provides a color filter including the cured layer.
[0011] Another embodiment provides a display device including the color filter.
[0012] Technical solution
[0013] One embodiment provides a curable composition comprising (A) a quantum dot including a first functional group represented by chemical formula 1 and a second functional group represented by chemical formula 2; and (B) a polymerizable compound.
[0014] [Chemical Formula 1]
[0015]
[0016] [Chemical Formula 2]
[0017]
[0018] In chemical formula 1 and chemical formula 2,
[0019] R 1 It is a substituted or unsubstituted C1 to C20 alkyl or a substituted or unsubstituted C6 to C20 aryl.
[0020] R 2 Vinyl group refers to substituted or unsubstituted vinyl groups.
[0021] L 1 and L 2 Each is independently an ether group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0022] L 3 and L 4 Each is independently a substituted or unsubstituted C1 to C20 alkylene or a substituted or unsubstituted C6 to C20 arylene.
[0023] L 5 It is an ether group, an ester group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0024] M is a divalent to tetravalent metal atom.
[0025] n is an integer from 1 to 10, and
[0026] m is an integer between 2 and 4.
[0027] Another embodiment provides a curable composition comprising: (A) quantum dots, a first surface modifier represented by Formula 11 and a second surface modifier represented by Formula 12, for surface modification; and (B) a polymerizable compound.
[0028] [Chemical Formula 11]
[0029]
[0030] [Chemical Formula 12]
[0031]
[0032] In chemical formulas 11 and 12,
[0033] R 1 It is a substituted or unsubstituted C1 to C20 alkyl or a substituted or unsubstituted C6 to C20 aryl.
[0034] R 2 For substituted or unsubstituted vinyl,
[0035] L 1 and L 2 Each is independently an ether group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0036] L 3 and L 4 Each is independently a substituted or unsubstituted C1 to C20 alkylene or a substituted or unsubstituted C6 to C20 arylene.
[0037] L 5 It is an ether group, an ester group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0038] M is a divalent to tetravalent metal atom.
[0039] n is an integer from 1 to 10, and
[0040] m is an integer between 2 and 4.
[0041] L 1 and L 3 Each can be independently a substituted or unsubstituted C1 to C20 alkylene group, and L 2It can be an ether group.
[0042] L 4 It can be a substituted or unsubstituted C1 to C20 alkylene group.
[0043] L 5 It can be an ester group.
[0044] The amount of the first functional group can be greater than the amount of the second functional group.
[0045] The weight of the first functional group can be 1 to 3 times the weight of the second functional group.
[0046] The amount of surface modification on the quantum dots by the first surface modifier can be greater than that by the second surface modifier.
[0047] The surface modification weight of the first surface modifier on the quantum dot can be 1 to 3 times that of the second surface modifier.
[0048] Polymerizable compounds may include compounds represented by chemical formula 3.
[0049] [Chemical Formula 3]
[0050]
[0051] In chemical formula 3,
[0052] L 6 It is a substituted or unsubstituted C1 to C10 alkylene group, a substituted or unsubstituted C3 to C20 cycloalkylene group, or an ether group ( -O- ),
[0053] L 7 and L 8 Each is independently a single bond or a substituted or unsubstituted C1 to C10 alkylene group.
[0054] R 3 and R 4 Each is independently a hydrogen atom or a substituted or unsubstituted C1 to C20 alkyl group.
[0055] The curable composition can have a viscosity of 15 centipoise (cP) to 30 centipoise.
[0056] The curable composition may be a solvent-free curable composition.
[0057] Solvent-free curable compositions may include 5% to 60% by weight of quantum dots based on the total amount of solvent-free curable compositions; and 40% to 95% by weight of polymerizable compounds.
[0058] The curable composition may also include a polymerization initiator, a light diffusing agent, a polymerization inhibitor, or a combination thereof.
[0059] Light diffusing agents may include barium sulfate, calcium carbonate, titanium dioxide, zirconium oxide, or combinations thereof.
[0060] Quantum dots can include non-cadmium-based luminescent materials.
[0061] Quantum dots can have a core / shell structure of InP / ZnS or a core / first shell / second shell structure of InP / ZnSe / ZnS.
[0062] Quantum dots may include a core comprising Ag, In, Ga, and S; and a shell comprising at least two selected from Ag, Ga, Zn, and S.
[0063] The curable composition may further include a solvent, and the curable composition may include 1% to 40% by weight of quantum dots, 1% to 20% by weight of polymerizable compound, and 40% to 80% by weight of solvent, based on the total weight of the curable composition.
[0064] The curable composition may also include malonic acid; 3-amino-1,2-propanediol; silane coupling agents; leveling agents; fluorinated surfactants; or combinations thereof.
[0065] Quantum dots can be green quantum dots.
[0066] Another embodiment provides a cured layer manufactured using the said curable composition.
[0067] Another embodiment provides a color filter including the cured layer.
[0068] Another embodiment provides a display device including the color filter.
[0069] The display device may also include a backlight unit (BLU), which may consist of three layers of blue light sources and one layer of green light sources, and the green light source may be an organic light emitting diode (OLED).
[0070] Other embodiments of the invention are included in the following detailed description.
[0071] Beneficial effects
[0072] In the case of curable compositions containing quantum dots, most attempts have focused on improving optical properties by increasing external quantum efficiency. However, the present invention relates to a curable composition containing quantum dots that improves frontal brightness by increasing light transmittance to approximately 530 nm rather than by increasing external quantum efficiency, and by using the curable composition containing quantum dots according to embodiments, frontal brightness can be significantly increased while minimizing the reduction in the light efficiency of the quantum dots. Attached Figure Description
[0073] Figure 1 A drawing illustrating the concept of green light emission methods in QD-OLED panels.
[0074] Figure 2 Drawings illustrating two different types of surface modifiers or functional groups involved in the curing of polymerizable compounds on the surface of quantum dots according to embodiments.
[0075] Figure 3 A cross-sectional scanning electron microscope (SEM) image of a cured layer manufactured using the curable composition according to Comparative Example 1.
[0076] Figure 4 A cross-sectional SEM image of a cured layer manufactured using the curable composition according to Example 1. Detailed Implementation
[0077] The embodiments of the present invention are described in detail below. However, these embodiments are exemplary, and the present invention is not limited thereto, and the scope of the claims defines the invention.
[0078] In this specification, unless otherwise specified, "alkyl group" refers to C1 to C20 alkyl, "alkenyl group" refers to C2 to C20 alkenyl, "cycloalkenyl group" refers to C3 to C20 cycloalkenyl, "heterocycloalkenyl group" refers to C3 to C20 heterocycloalkenyl, "aryl group" refers to C6 to C20 aryl, "arylalkyl group" refers to C6 to C20 arylalkyl, "alkylene group" refers to C1 to C20 alkylene, "arylene group" refers to C6 to C20 arylene, "alkylarylene group" refers to C6 to C20 alkylarylene, "heteroarylene group" refers to C3 to C20 heteroarylene, and "alkoxylene group" refers to C1 to C20 alkoxy.
[0079] In this specification, unless otherwise specifically defined, "substituted" means the replacement of at least one hydrogen atom with a substituent selected from the following: halogen atom (F, Cl, Br, or I), hydroxyl, C1 to C20 alkoxy, nitro, cyano, amino, imino group, azido group, amidino group, hydrazino group, hydrazono group, carbonyl group, carbamyl group, thiol group. (group), ester group, ether group, carboxyl group or salt thereof, sulfonic acid group or salt thereof, phosphate group or salt thereof, C1 to C20 alkyl, C2 to C20 alkenyl, C2 to C20 alkynyl, C6 to C20 aryl, C3 to C20 cycloalkyl, C3 to C20 cycloalkenyl, C3 to C20 cycloalkynyl, C2 to C20 heterocyclic alkyl, C2 to C20 heterocyclic alkenyl, C2 to C20 heterocyclic alkynyl, C3 to C20 heteroaryl or combinations thereof.
[0080] In this specification, unless otherwise specified, “hetero” means a heteroatom that contains at least one N, O, S, and P atom in its chemical formula.
[0081] In this specification, unless otherwise specified, “(meth)acrylate” means both “acrylate” and “methacrylate”, and “(meth)acrylic acid” means both “acrylic acid” and “methacrylic acid”.
[0082] In this specification, unless otherwise specified, the term "combination" refers to mixing or copolymerization.
[0083] In this specification, unless otherwise defined, hydrogen is bonded at the position where a chemical bond is not shown in the chemical formula.
[0084] Furthermore, unless otherwise defined in this specification, " "" refers to the connection point with the same atom or chemical formula or different atom or chemical formula.
[0085] In the display device according to an embodiment, the backlight unit (BLU) of the QD-OLED product consists of blue (3 layers) and green (1 layer) OLED layers. Blue OLED light induces the green quantum dot layer to emit light, while green OLED light passes through the green quantum dot layer and is emitted. Therefore, the light emitted by the quantum dots combines with the light emitted by the quantum dots to present the overall front brightness. (See...) Figure 1 )
[0086] However, since the backlight units of currently commercially available products only consist of blue and green layers, such as Figure 1 The emission method shown applies only to green quantum dot pixels (green QD pixels) and does not provide significant gain in the red domain.
[0087] However, since the brightness of display devices is typically determined primarily by green light intensity, and various attempts and efforts are continuously made to improve brightness, based on... Figure 1 In the light-emitting method shown, besides the light emission of the quantum dots themselves, the transmittance of the green OLED contributes significantly. Therefore, it is necessary to increase the transmittance of the quantum dot layer while maintaining a certain level of quantum dot light emission. The embodiments relate to a curable composition containing quantum dots that can increase the transmittance of the quantum dot layer based on the aforementioned light-emitting method.
[0088] According to an embodiment, the curable composition includes (A) quantum dots, including a first functional group represented by chemical formula 1 and a second functional group represented by chemical formula 2; and (B) a polymerizable compound; or the curable composition includes: (A) quantum dots, surface modified by a first surface modifier represented by chemical formula 11 and a second surface modifier represented by chemical formula 12; and (B) a polymerizable compound.
[0089] [Chemical Formula 1]
[0090]
[0091] [Chemical Formula 2]
[0092]
[0093] [Chemical Formula 11]
[0094]
[0095] [Chemical Formula 12]
[0096]
[0097] In chemical formulas 1, 2, 11, and 12,
[0098] R 1 It is a substituted or unsubstituted C1 to C20 alkyl or a substituted or unsubstituted C6 to C20 aryl.
[0099] R 2 For substituted or unsubstituted vinyl,
[0100] L 1 and L 2 Each is independently an ether group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0101] L 3 and L 4 Each is independently a substituted or unsubstituted C1 to C20 alkylene or a substituted or unsubstituted C6 to C20 arylene.
[0102] L 5 It is an ether group, an ester group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group.
[0103] M is a divalent to tetravalent metal atom.
[0104] n is an integer from 1 to 10, and
[0105] m is an integer between 2 and 4.
[0106] The components constituting a curable composition according to one embodiment are described in detail below.
[0107] quantum dots
[0108] To improve frontal brightness, the light efficiency of quantum dots must be at least 10% higher than conventional methods, which may be achieved by excessively increasing the content of inorganic materials such as quantum dots to 50% or higher. However, the higher the content of inorganic materials in the curable composition, the higher the viscosity of the composition, which may lead to another problem such as inkjet printing difficulties. The inventors have confirmed that by choosing to increase the transmittance of the curable composition at approximately 530 nm, rather than improving the light efficiency of the quantum dots in the curable composition, as a means of increasing frontal brightness, frontal brightness can be significantly increased without minimizing the degradation of the light efficiency of quantum dots, especially green quantum dots, thus completing the present invention. Traditionally, various methods for improving frontal brightness have existed, but the present invention differs from the prior art by disclosing a curable composition that improves frontal brightness by increasing the transmittance at approximately 530 nm.
[0109] According to one embodiment, the quantum dots in the curable composition include two different types of functional groups (a first functional group derived from a first surface modifier and a second functional group derived from a second surface modifier), thereby significantly improving frontal brightness by improving transmittance at 530 nm without significantly increasing external quantum efficiency.
[0110] Specifically, the first and second functional groups can readily participate in the solidification on the quantum dot surface together with the polymerizable compound (with carbon-carbon double bonds at the ends), which will be described later (see [link to article]). Figure 2 This improves the aggregation of inorganic particles or quantum dot particles in curable components.
[0111] In other words, according to one embodiment, the aggregation of inorganic particles or quantum dot particles in the ink matrix (curable composition) that hinders the light transmission of green OLEDs can be improved. Therefore, uniformly dispersing quantum dot particles in the curable composition (a photocurable matrix) is a technical challenge, which can be solved by controlling the functional groups of the surface-modified ligands of the quantum dots as described above to minimize the mismatch between the quantum dot surface and the polymerizable compound matrix, thereby improving the light transmittance of green OLEDs.
[0112] In this regard, the objective and technical challenge of the present invention is to improve the single-film transmittance of the green quantum dot curing layer, thereby increasing the transmittance of the green OLED, while maintaining the luminous efficiency of the quantum dots to a certain extent by using curable components with the same or similar inorganic material content as conventional ones, thereby ultimately improving the front brightness.
[0113] In terms of composition, reducing the content of inorganic particles or scatterers can easily increase the single-film transmittance of the quantum dot-cured layer. This may lead to a decrease in light scattering intensity, thereby reducing the luminous efficiency of the final quantum dot layer. Furthermore, there may be another drawback: the ratio of frontal brightness may be distorted.
[0114] Therefore, simply increasing or decreasing the content of inorganic particles, etc., may not meet the latest demands for superior display color characteristics. However, one embodiment meets these latest demands, wherein the ligands on the quantum dot surface participate in the overall matrix curing while maintaining the content of quantum dots or scatterers, effectively improving the linearity of green OLED light transmitted through the quantum dot matrix layer.
[0115] On the other hand, since the curable composition according to one embodiment has the same or similar inorganic particle content as the prior art, the composition can also have a low viscosity of 15 cP to 30 cP at room temperature (15 to 30 degrees Celsius).
[0116] For example, L 1 and L 3 Each can be independently a substituted or unsubstituted C1 to C20 alkylene group, and L 2 It can be an ether group.
[0117] For example, L 4 It can be a substituted or unsubstituted C1 to C20 alkylene group.
[0118] For example, L 5 It can be an ester group ( -C(=O)O- or -OC(=O)- ).
[0119] For example, the first functional group may be included in the same or greater amount as the second functional group, and the first surface-modifying material may be included in the same or greater amount as the second surface-modifying material to surface-modify the quantum dots. Specifically, the weight of the first functional group may be 1 to 3 times, for example 1 to 2 times, for example 1 to 1.5 times, or for example 1 to 1.4 times the weight of the second functional group, and the first surface-modifying material may be used to surface-modify the quantum dot surface in an amount that is 1 to 3 times, for example 1 to 2 times, for example 1 to 1.5 times, or for example 1 to 1.4 times the weight of the second surface-modifying material. In this case, the mismatch between the surface-modified quantum dot surface and the polymerizable compound described later can be minimized, further improving the light transmittance of the green OLED, and exhibiting high light retention over time and excellent lightfastness. On the other hand, if the first functional group is included in a lower amount than the second functional group, or if the first surface-modifying material is included in a lower amount than the second surface-modifying material, the light retention may decrease again, and the improvement in transmittance may be insignificant, resulting in almost no improvement in front brightness. That is, according to one embodiment, as the first functional group is included in an amount equal to or greater than the content of the second functional group, and simultaneously, in the total content of surface-modified functional groups on the quantum dot, the relative content of the first functional group decreases and the relative content of the second functional group increases, light retention rate, light resistance reliability, and light transmittance can all be improved. For example, the first and second functional groups can be used to surface modify the quantum dot in a weight ratio of 70:30 to 50:50, such as 60:40 to 50:50. Similarly, according to one embodiment, as the first surface-modifying material is included in an amount equal to or greater than the content of the second surface-modifying material, and simultaneously, in the total content of surface-modifying materials on the quantum dot, the relative content of the first surface-modifying material decreases and the relative content of the second surface-modifying material increases, light retention rate, light resistance reliability, and light transmittance can all be improved. For example, the first surface modifier and the second surface modifier can be used to surface modify the quantum dots in a weight ratio of 70:30 to 50:50, such as 60:40 to 50:50.
[0120] For example, quantum dots can have the largest fluorescence emission wavelength in the range of 500 nanometers to 680 nanometers.
[0121] For example, when the curable composition according to the embodiment is a solvent-free curable composition, quantum dots may be included in an amount of 5% to 60% by weight, for example, in an amount of 10% to 60% by weight, for example, in an amount of 20% to 60% by weight, for example, in an amount of 30% to 50% by weight. When quantum dots are included within the above range, high light retention and light efficiency can be achieved even after curing.
[0122] For example, when the curable composition according to the embodiment is a curable composition containing a solvent, it may contain 1% to 40% by weight, for example, 3% to 30% by weight, of quantum dots based on the total amount of the curable composition. When quantum dots within the above range are included, the light conversion efficiency is improved, and the patterning and developing properties are not impaired, thus improving processability is obtained.
[0123] For example, quantum dots absorb light in the wavelength range of 360 nm to 780 nm, such as 400 nm to 780 nm, and emit fluorescence in the wavelength range of 500 nm to 700 nm, such as 500 nm to 580 nm, or in the wavelength range of 600 nm to 680 nm. That is, quantum dots can have the maximum fluorescence emission wavelength (fluorescence λ) in the 500 nm to 680 nm range. em ).
[0124] Quantum dots can independently have a full width at half maximum (FWHM) of 20 to 100 nanometers, for example, 20 to 50 nanometers. When quantum dots have a full width at half maximum (FWHM) within this range, color reproducibility is increased due to high color purity when used as color materials in color filters.
[0125] Quantum dots can be organic materials, inorganic materials, or hybrids of organic and inorganic materials independently.
[0126] Quantum dots may each independently comprise a core and a shell surrounding the core, and the core and the shell may have structures such as cores of groups II-IV, III-V and similar groups, core / shell, core / first shell / second shell, alloy, alloy / shell, etc., but are not limited to these.
[0127] For example, the core may contain at least one material selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, GaN, GaP, GaAs, InP, InAs, and alloys thereof, but is not limited to this. The shell surrounding the core may contain at least one material selected from CdSe, ZnSe, ZnS, ZnTe, CdTe, PbS, TiO, SrSe, HgSe, and alloys thereof, but is not limited to this.
[0128] In this embodiment, due to the significant increase in environmental concerns worldwide in recent years and the strengthening of restrictions on toxic materials, environmentally friendly cadmium-free luminescent materials (InP / ZnS, InP / ZnSe / ZnS, etc.) with extremely low quantum efficiency (quantum yield) are used instead of luminescent materials with cadmium-like cores, but are not limited to this.
[0129] In embodiments, a quantum dot may comprise a core containing Ag, In, Ga, and S; and a shell containing at least two (or at least three) of Ag, Ga, Zn, and S. In this case, the quantum dot may have one or more ligands. For example, the quantum dot may include, but is not limited to, a first ligand containing a halide, a second ligand containing an alkyl and / or alkoxyamine group, or a combination thereof.
[0130] For quantum dots with a core / shell structure, the size (average particle diameter) of each quantum dot, including the shell, can be from 1 nanometer to 15 nanometers, for example, from 5 nanometers to 15 nanometers.
[0131] For example, quantum dots can independently include red quantum dots, green quantum dots, or combinations thereof. Red quantum dots can independently have an average particle size of 10 nanometers to 15 nanometers. Green quantum dots can independently have an average particle size of 5 nanometers to 8 nanometers.
[0132] For example, quantum dots can be green quantum dots.
[0133] On the other hand, regarding the dispersion stability of quantum dots, the curable composition according to the embodiments may further include a dispersant. The dispersant contributes to the uniform dispersion of light conversion materials such as quantum dots in the curable composition and may include nonionic, anionic, or cationic dispersants. Specifically, the dispersant may be a polyalkylene glycol or its ester, polyoxyalkylene, polyhydric alcohol ester alkylene oxide addition product, alcohol alkylene oxide addition product, sulfonate ester, sulfonate salt, carboxylate ester, carboxylate salt, alkyl amide alkylene oxide addition product, alkylamine, etc., and may be used alone or in mixtures of two or more. The dispersant may be used in an amount from 0.1% by weight to 100% by weight, for example, from 10% by weight to 20% by weight, based on the solids content of the light conversion material such as quantum dots.
[0134] For example, the first functional group represented by chemical formula 1 can be represented by chemical formula 1-1, and the first surface-modifying material represented by chemical formula 11 can be represented by chemical formula Q.
[0135] [Chemical Formula 1-1]
[0136]
[0137] [Chemical Formula Q]
[0138]
[0139] For example, the second functional group represented by chemical formula 2 can be represented by chemical formula 2-1, and the second surface-modifying material represented by chemical formula 12 can be represented by chemical formula R.
[0140] [Chemical Formula 2-1]
[0141]
[0142] [Chemical formula R]
[0143]
[0144] For example, quantum dots can be further surface-modified with surface-modifying materials containing polar groups with different structures, in addition to those represented by the chemical formula Q, to greatly facilitate the preparation of high-concentration or highly densified quantum dot dispersions (improving the dispersibility of quantum dots in polymerizable compounds) and enhance light efficiency. Surface-modifying materials with polar groups having different structures may have structural advantages in realizing solvent-free curable compositions.
[0145] For example, surface-modified materials with polar groups having different structures can have structures that have high affinity for the chemical structure of polymerizable compounds, which will be described later.
[0146] For example, surface-modified materials with polar groups having different structures can be represented by any of the chemical formulas A to P, but are not necessarily limited to these.
[0147] [Chemical Formula A]
[0148]
[0149] [Chemical Formula B]
[0150]
[0151] [Chemical formula C]
[0152]
[0153] [Chemical formula D]
[0154]
[0155] In chemical formula D, m1 is an integer from 0 to 10.
[0156] [Chemical Formula E]
[0157]
[0158] [Chemical formula F]
[0159]
[0160] [Chemical formula G]
[0161]
[0162] [Chemical formula H]
[0163]
[0164] [Chemical Formula I]
[0165]
[0166] [Chemical Formula J]
[0167] [Chemical formula K]
[0168]
[0169] [Chemical formula L]
[0170]
[0171] [Chemical Formula M]
[0172]
[0173] [Chemical formula N]
[0174]
[0175] [Chemical formula O]
[0176]
[0177] [Chemical formula P]
[0178]
[0179] If a surface modifier with a structure different from that of the chemical formula Q is used, the quantum dots may be further surface modified. When the quantum dots that have been surface modified with the surface modifier are added to and mixed with the polymerizable compound matrix, a very transparent dispersion can be obtained, which can be used as a standard to check whether the quantum dots have been well surface modified.
[0180] polymerizable compounds
[0181] The curable composition according to the embodiments may include a polymerizable compound, and the polymerizable compound may have a carbon-carbon double bond at its end.
[0182] The content of polymerizable compounds with terminal carbon-carbon double bonds in the total amount of solvent-free curable composition can be from 40% to 95% by weight, for example, from 50% to 90% by weight. When polymerizable compounds with terminal carbon-carbon double bonds are included within the range described above, solvent-free curable compositions with viscosity that enables inkjet printing can be prepared, and the quantum dots in the prepared solvent-free curable compositions can have improved dispersibility, thereby improving optical properties.
[0183] For example, polymerizable compounds with carbon-carbon double bonds at the ends can have molecular weights ranging from 170 g / mol to 1000 g / mol. When the molecular weight of a polymerizable compound with carbon-carbon double bonds at the ends is within the above range, it can be advantageous for inkjet printing because the viscosity of the composition does not increase without impairing the optical properties of the quantum dots.
[0184] For example, polymerizable compounds with carbon-carbon double bonds at the ends can be represented by chemical formula 3, but are not necessarily limited to this.
[0185] [Chemical Formula 3]
[0186]
[0187] In chemical formula 3,
[0188] L 6 It is a substituted or unsubstituted C1 to C10 alkylene group, a substituted or unsubstituted C3 to C20 cycloalkylene group, or an ether group ( -O- ),
[0189] L 7 and L 8 Each is independently a single bond or a substituted or unsubstituted C1 to C10 alkylene group.
[0190] R 3 and R 4 Each is independently a hydrogen atom or a substituted or unsubstituted C1 to C20 alkyl group.
[0191] For example, polymerizable compounds with carbon-carbon double bonds at the ends can be represented by chemical formula 3-1, chemical formula 3-2 or chemical formula 3-3, but are not necessarily limited to these.
[0192] [Chemical Formula 3-1]
[0193]
[0194] [Chemical Formula 3-2]
[0195]
[0196] [Chemical Formula 3-3]
[0197]
[0198] For example, polymerizable compounds with carbon-carbon double bonds at the ends may also include ethylene glycol diacrylate, triethylene glycol diacrylate, 1,4-butanedioldiacrylate, 1,6-hexanedioldiacrylate, neopentyl glycol diacrylate, pentaerythritol diacrylate, pentaerythritoltriacrylate, dipentaerythritol diacrylate, dipentaerythritoltriacrylate, dipentaerythritoltriacrylate, dipentaerythritolpentaacrylate, pentaerythritolhexaacrylate, and bisphenol A diacrylate. diacrylate), trimethylolpropanetriacrylate, novolacepoxyacrylate, ethylene glycoldimethacrylate, triethylene glycoldimethacrylate, propylene glycoldimethacrylate, 1,4-butanedioldimethacrylate, 1,6-hexanedioldimethacrylate, or combinations thereof, except for the compounds of formulas 3-1 to 3-3 above.
[0199] In addition to polymerizable compounds having carbon-carbon double bonds at the ends, the composition may also include monomers commonly used in conventional thermosetting or photocurable compositions. For example, monomers may also include oxetane-based compounds, such as bis[1-ethyl (3-oxetanyl)]methyl ether.
[0200] Furthermore, when the curable component includes a solvent, the polymerizable compound may be included in an amount of 1% to 20% by weight, 1% to 15% by weight, for example, 5% to 15% by weight, based on the total amount of the curable component. Including the polymerizable compound within the above range can improve the optical properties of the quantum dots.
[0201] Light diffusing agent
[0202] The curable composition according to the embodiments may further include a light diffusing agent.
[0203] For example, light diffusing agents may include barium sulfate (BaSO4), calcium carbonate (CaCO3), titanium dioxide (TiO2), zirconium oxide (ZrO2), or combinations thereof.
[0204] Light diffusing agents can reflect light that has not been absorbed by the quantum dots and allow the quantum dots to reabsorb the reflected light. In other words, light diffusing agents can increase the amount of light absorbed by the quantum dots and increase the light conversion efficiency of the curable components.
[0205] Light diffusing agents can have an average particle size (D) of 150 nm to 250 nm. 50 Specifically, the average particle size of the light diffusing agent is between 180 nanometers and 230 nanometers. When the average particle size of the light diffusing agent is within this range, it can have a better light diffusion effect and increase the light conversion efficiency.
[0206] Light diffusing agents can act as scatterers, and either rutile or anatase types can be used. However, in terms of improving external quantum efficiency, rutile types may be more advantageous than anatase types.
[0207] The content of the light diffusing agent can be from 1% to 20% by weight, for example, from 2% to 15% by weight, or from 3% to 10% by weight, based on the total amount of the curable components. When the content of the light diffusing agent is less than 1% by weight, it is difficult to expect to improve the light conversion efficiency by using the light diffusing agent, and when its content is greater than 20% by weight, quantum dot deposition problems may occur.
[0208] Polymerization initiator
[0209] The curable composition according to the embodiments may further include a polymerization initiator, such as a photopolymerization initiator, a thermal polymerization initiator, or a combination thereof.
[0210] The polymerization initiator may be an initiator commonly used in curable components, and may include, for example, acetophenone compounds, benzophenone compounds, thiazoline compounds, benzoin-based compounds, triazine compounds, oxime compounds, amino ketone compounds, etc., but is not necessarily limited to these.
[0211] Examples of acetophenone compounds include 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylacetophenone, p-butyltrichloroacetophenone, p-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one.
[0212] Examples of benzophenone compounds include benzophenone, benzoyl benzoate, benzoyl methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone, etc.
[0213] Examples of thiazoxone compounds include thiazoxone, 2-methylthiazoxone, isopropylthiazoxone, 2,4-diethylthiazoxone, 2,4-diisopropylthiazoxone, 2-chlorothiazoxone, etc.
[0214] Examples of benzophenone compounds include benzophenone, benzophenone methyl ether, benzophenone ethyl ether, benzophenone isopropyl ether, benzophenone isobutyl ether, benzyl dimethylketal, etc.
[0215] Examples of triazine compounds include 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphthol-1-yl)-4,6-bis(trichloromethyl)-s-triazine (2-(naphthol-1-yl)-4,6-bis(trichloromethyl)-s-triazine) Examples of triazine include ho-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphtho-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-4-bis(trichloromethyl)-6-piperonyl-s-triazine, and 2-4-bis(trichloromethyl)-6-(4-methoxystyryl)-s-triazine.
[0216] Examples of oxime compounds include O-acyloxime compounds, 2-(O-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octandione, 1-(O-acetyloxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, and O-ethoxycarbonyl-α-oxyamino-1-phenylpropan-1-one. Specific examples of O-acyloxime compounds include 1,2-octanedione, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-but-1-one, 1-(4-phenylsulfanylphenyl)-butane-1,2-dione 2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octane-1,2-dione 2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octane-1-one oxime-O-acetate, and 1-(4-phenylsulfanylphenyl)-but-1-one oxime-O-acetate.
[0217] Examples of amino ketone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, etc.
[0218] In addition to the compounds mentioned above, photopolymerization initiators may also include carbazole compounds, diketone compounds, thioonium borate compounds, diazo compounds, imidazole compounds, diimidazole compounds, etc.
[0219] Photopolymerization initiators can be used with photosensitizers that can induce a chemical reaction by absorbing light, becoming excited, and then transferring their energy.
[0220] Examples of photosensitizers include tetraethylene glycol bis-3-mercaptopropionate, pentaerythritol tetra-3-mercaptopropionate, and dipentaerythritol tetra-3-mercaptopropionate.
[0221] Examples of thermal polymerization initiators may be peroxides, specifically benzoyl peroxide, dibenzoyl peroxide, lauroyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cyclohexane peroxide, methyl ethyl ketone peroxide, hydrogen peroxide (e.g., tert-butyl hydrogen peroxide, cumene hydrogen peroxide), dicyclohexyl percarbonate, 2,2-azobis(isobutyronitrile), tert-butyl perbenzoate, etc., such as 2,2'-azobis-2-methylpropionitrile, but not limited thereto, and any known to those skilled in the art may be used.
[0222] The polymerization initiator may be included in an amount from 0.1 wt% to 5 wt%, for example, from 1 wt% to 4 wt%, based on the total amount of the curable component. When the polymerization initiator is included in the range described above, it is possible to obtain excellent reliability due to sufficient curing during exposure or thermal curing, and it is possible to prevent degradation of transmittance due to non-reactive initiators, thereby preventing degradation of the optical properties of the quantum dots.
[0223] Adhesive resin
[0224] According to one embodiment, the curable composition may further include an adhesive resin.
[0225] Adhesive resins may include acrylic resins, calomel resins, epoxy resins, or combinations thereof.
[0226] The acrylic resin may be a copolymer of a first vinyl unsaturated monomer and a second vinyl unsaturated monomer that can be copolymerized therewith, and may be a resin containing at least one repeating acrylic unit.
[0227] Specific examples of acrylic adhesive resins may include polyphenyl methacrylate, (meth)acrylic acid / phenyl methacrylate copolymer, (meth)acrylic acid / phenyl methacrylate / styrene copolymer, (meth)acrylic acid / phenyl methacrylate / 2-hydroxyethyl methacrylate copolymer, (meth)acrylic acid / phenyl methacrylate / styrene / 2-hydroxyethyl methacrylate copolymer, etc., but are not limited thereto, and may be used alone or as a mixture of two or more.
[0228] The weight-average molecular weight of acrylic adhesive resins can range from 5,000 g / mol to 15,000 g / mol. When acrylic adhesive resins have a weight-average molecular weight within this range, their adhesion to the substrate, physical properties, and chemical properties are improved, and their viscosity is appropriate.
[0229] Acrylic resins can have an acid value ranging from 80 mgKOH / g to 130 mgKOH / g. When acrylic resins have an acid value within this range, pixel patterns can have excellent resolution.
[0230] Cado resins can be used in conventional curable resin (or photosensitive resin) compositions, and can be used, for example, as disclosed in Korean Patent Application Publication No. 10-2018-0067243, but are not limited thereto.
[0231] Carbomer resins can be prepared, for example, by mixing at least two of the following compounds: fluorinated compounds such as 9,9-bis(4-oxiranylmethoxyphenyl)fluorene; anhydride compounds such as benzoyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, trimellitic dianhydride, cyclobutanetetracarboxylic dianhydride, perylenetetracarboxylic dianhydride, tetrahydrofurantetracarboxylic dianhydride, and tetrahydrophthalic anhydride; diol compounds such as ethylene glycol, propylene glycol, and polyethylene glycol; alcohol compounds such as methanol, ethanol, propanol, n-butanol, cyclohexanol, and benzyl alcohol; solvent compounds such as propylene glycol methyl ethyl acetate and N-methylpyrrolidone; phosphorus compounds such as triphenylphosphine; and amine or ammonium salt compounds such as tetramethylammonium chloride, tetraethylammonium bromide, benzyl diethylamine, triethylamine, tributylamine, or benzyl triethylammonium chloride.
[0232] The weight-average molecular weight of the calotype adhesive resin can be from 500 g / mol to 50,000 g / mol, for example from 1,000 g / mol to 30,000 g / mol. When the weight-average molecular weight of the calotype adhesive resin is within this range, satisfactory patterns can be formed without residues during the production of the cured layer and without loss of film thickness during the development of the solvent-based curable composition.
[0233] When the adhesive resin is a caloric resin, the developability of the curable composition (especially curable compositions including the adhesive resin) is improved, and the sensitivity during photocuring is good, thus improving the fine patterning properties.
[0234] Epoxy resins can be monomers or oligomers that can be thermally polymerized, and can include compounds having carbon-carbon unsaturated bonds and carbon-carbon cyclic bonds.
[0235] Epoxy resins may include, but are not limited to, bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic varnish type epoxy resin, alicyclic epoxy resin and aliphatic polyglycidyl ether.
[0236] Currently, its available products include bisphenol epoxy resins, such as YX4000, YX4000H, YL6121H, YL6640, or YL6677 from YukaShell Epoxy Co., Ltd.; cresol-phenolic varnish-type epoxy resins, such as EOCN-102, EOCN-103S, EOCN-104S, EOCN-1020, EOCN-1025, and EOCN-1027 from Nippon Kayaku Co., Ltd., and EPIKOTE180S75 from YukaShell Epoxy Co., Ltd.; and bisphenol A epoxy resins, such as EPIKOTE from YukaShell Epoxy Co., Ltd. 1001, 1002, 1003, 1004, 1007, 1009, 1010, and 828; bisphenol F type epoxy resins, such as EPIKOTE 807 and 834 from Yuxiang Shell Epoxy Co., Ltd.; phenolic varnish type epoxy resins, such as EPIKOTE 152, 154, and 157H65 from Yuxiang Shell Epoxy Co., Ltd., and EPPN 201 and 202 from Nippon Kayaku Co., Ltd.; other cyclic aliphatic epoxy resins, such as CY175, CY177, and CY179 from Ciba-Geigy AG, ERL-4234, ERL-4299, ERL-4221, and ERL-4206 from Union Carbide Corporation (UCC), and Showa Denko Co., Ltd. Shodyne 509 from KK, ARALDITE CY-182, CY-192 and CY-184 from Ciba Geggi, Epichron 200 and 400 from Dainippon Ink and Chemicals, Inc., EPIKOTE 871, 872 and EP1032H60 from Yuka Shell Epoxy, ED-5661 and ED-5662 from Celanese Coatings Co., Ltd.; aliphatic polyglycidyl ethers, such as EPIKOTE 190P and 191P from Yuka Shell Epoxy, Epolite 100MF from Kyoesha Yushi Co., Ltd., and Epiol TMP from Nippon Yushi Co., Ltd., etc.
[0237] For example, when the curable composition according to one embodiment is a solvent-free curable composition, the content of adhesive resin may be from 0.5% to 10% by weight, for example, from 1% to 5% by weight, based on the total amount of the curable composition. In this case, the heat resistance and chemical resistance of the solvent-free curable composition can be improved, and the storage stability of the composition can also be improved.
[0238] For example, when the curable composition according to one embodiment is a curable composition including a solvent, the content of adhesive resin may be from 1% to 30% by weight, for example, from 3% to 20% by weight, based on the total amount of the curable composition. In this case, pattern characteristics, heat resistance, and chemical resistance can be improved.
[0239] Other additives
[0240] To improve the stability and dispersibility of quantum dots, the curable composition according to the embodiments may further include a polymerization inhibitor.
[0241] Polymerization inhibitors may include, but are not limited to, hydroquinone-based compounds, catechol-based compounds, or combinations thereof. When the curable composition according to the embodiments further comprises hydroquinone compounds, catechol compounds, or combinations thereof, room-temperature crosslinking during exposure after coating the curable composition can be prevented.
[0242] For example, hydroquinone compounds, catechol compounds, or combinations thereof may include hydroquinone, methylhydroquinone, methoxyhydroquinone, tributylhydroquinone, 2,5-di-t-butylhydroquinone, 2,5-bis(1,1-dimethylbutyl)hydroquinone, 2,5-bis(1,1,3,3-tetramethylbutyl)hydroquinone, catechol, tributylcatechol, 4-methoxyphenol, pyrogallol, 2,6-di-t-butyl-4-methylphenol, 2-naphthol, tris(N-hydroxy-N-nitrosophenylaminato-O,O')aluminum, or combinations thereof, but are not necessarily limited thereto.
[0243] Hydroquinone compounds, catechol compounds, or combinations thereof can be used in dispersed form. The content of the polymerization inhibitor in dispersed form can be from 0.001% to 3% by weight, for example, from 0.01% to 2% by weight, based on the total amount of the curable component. When the polymerization inhibitor is included within the above range, the time elapsed at room temperature can be addressed, while preventing sensitivity degradation and surface peeling.
[0244] In addition, the curable composition according to the embodiments may also include malonic acid; 3-amino-1,2-propanediol; silane coupling agents; leveling agents; fluorinated surfactants; or combinations thereof, to improve heat resistance and reliability.
[0245] For example, the curable composition according to the embodiments may further include a silane coupling agent having reactive substituents (such as vinyl, carboxyl, methacryloyloxy, isocyanate, epoxy, etc.) to improve the tight contact properties with the substrate.
[0246] Examples of silane coupling agents may include trimethoxysilylbenzoic acid, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, γ-isocyanate propyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, β-(epoxycyclohexyl)ethyltrimethoxysilane, etc. These may be used alone or in mixtures of two or more.
[0247] Based on 100 parts by weight of curable composition, silane coupling agents can be used in amounts from 0.01 parts by weight to 10 parts by weight. When silane coupling agents are included within this range, close contact properties, storage capacity, etc., can be improved.
[0248] In addition, the curable composition may also contain surfactants (such as fluorinated surfactants) as needed to improve coating properties and inhibit spot formation, i.e., improve leveling performance.
[0249] Fluorinated surfactants can have a low weight-average molecular weight of 4,000 g / mol to 10,000 g / mol, and more specifically 6,000 g / mol to 10,000 g / mol. Furthermore, fluorinated surfactants can have a surface tension of 18 mN / m to 23 mN / m (measured in a 0.1% solution of polyethylene glycol monomethyl ether acetate (PGMEA)). When fluorinated surfactants have a weight-average molecular weight and surface tension within the aforementioned range, leveling performance can be further improved, and excellent properties can be provided when applied as a high-speed slit coating, as this reduces film defects by preventing spot formation and suppressing vapor generation during high-speed coating.
[0250] An example of a fluorinated surfactant is BM-1000 from BM Chemie Inc. ® and BM-1100 ®MEGAFACE F142D from Dainippon Ink Kagaku Kogyo Co., Ltd. ® F 172 ® F 173 ® And F 183 ® FULORADFC-135 from Sumitomo 3M Co., Ltd. ® FULORAD FC-170C ® FULORAD FC-430 ® and FULORAD FC-431 ® ; SURFLON S-112 from Asahi Glass Co., Ltd. ® SURFLON S-113 ® SURFLON S-131 ® SURFLON S-141 ® and SURFLON S-145 ® And Toray Silicone Co., Ltd.'s SH-28PA ® SH-190 ® SH-193 ® SZ-6032 ® and SF-8428 ® etc.; DIC Co., Ltd.'s F-482, F-484, F-478, F-554, etc.
[0251] Furthermore, the curable composition according to the embodiments may contain silicone surfactants other than fluorinated surfactants. Specific examples of silicone surfactants may be, but are not limited to, TSF400, TSF401, TSF410, TSF4440 and similar products from Toshiba Silicone Co., Ltd.
[0252] The surfactant content can be from 0.01 parts by weight to 5 parts by weight, for example, from 0.1 parts by weight to 2 parts by weight, based on 100 parts by weight of the curable composition. When the surfactant content is within the said range, fewer foreign matter is generated in the sprayed composition.
[0253] In addition, unless the properties deteriorate, the curable composition according to the embodiments may also contain a predetermined amount of other additives, such as antioxidants, stabilizers, etc.
[0254] solvent
[0255] Additionally, the curable composition according to the embodiments may further include a solvent.
[0256] Solvents may include, for example, alcohols such as methanol and ethanol; glycol ethers such as ethylene glycol methyl ether, ethylene glycol ethyl ether, and propylene glycol methyl ether; cellosol acetates such as methyl cellosol acetate, ethyl cellosol acetate, and diethyl cellosol acetate; carbitols such as methyl ethyl carbitol, diethyl carbitol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol diethyl ether; propylene glycol alkyl ether acetates such as propylene glycol monomethyl ether acetate and propylene glycol propyl ether acetate; and ketones such as methyl ethyl ketone, cyclohexanone, 4-hydroxy-4-methyl-2-pentanone, and methyl n-acetone. 1. Methyl n-Butyl ketone, methyl n-pentanone, 2-Heptanone, etc.; 2. Saturated aliphatic monocarboxylic acid alkyl esters, such as ethyl acetate, n-butyl acetate, isobutyl acetate, etc.; 3. Lactate esters, such as methyl lactate, ethyl lactate, etc.; 4. Alkyl glycolate esters, such as methyl glycolate, ethyl glycolate, butyl glycolate, etc.; 5. Alkyl acetate alkoxy esters, such as methyl methoxyacetate, ethyl methoxyacetate, butyl methoxyacetate, methyl ethoxyacetate, ethyl ethoxyacetate, etc.; 6. Alkyl 3-hydroxypropionic acid esters, such as methyl 3-hydroxypropionic acid, ethyl 3-hydroxypropionic acid, etc.; 7. Alkyl 3-alkoxypropionic acid esters, such as methyl 3-methoxypropionic acid, methyl 3-hydroxypropionic acid, etc. Ethyl hydroxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, etc.; alkyl 2-hydroxypropionates, such as methyl 2-hydroxypropionate, ethyl 2-hydroxypropionate, propyl 2-hydroxypropionate, etc.; alkyl 2-alkoxypropionates, such as methyl 2-methoxypropionate, ethyl 2-methoxypropionate, ethyl 2-ethoxypropionate, methyl 2-ethoxypropionate, etc.; alkyl 2-hydroxy-2-methylpropionates, such as methyl 2-hydroxy-2-methylpropionate, ethyl 2-hydroxy-2-methylpropionate, etc.; alkyl 2-alkoxy-2-methylpropionates, such as methyl 2-methoxy-2-methylpropionate, methyl 2-ethoxypropionate, etc. Ethyl 2-methylpropionate, etc.; esters, such as 2-hydroxyethyl propionate, 2-hydroxy-2-methylethyl propionate, hydroxyethyl acetate, 2-hydroxy-3-methylmethyl butyrate, etc.; or keto esters, such as ethyl pyruvate, etc., and in addition, may be N-methylformamide, N,N-dimethylformamide, N-methylformaniline, N-methylacetamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, benzyl ethyl ether, dihexyl ether, acetylacetone, isophorone, hexanoic acid, octanoic acid, 1-octanol, 1-nonanol, benzyl alcohol, benzyl acetate, ethyl benzoate, diethyl oxalate, diethyl maleate, γ-butyrolactone, ethylene carbonate, propylene carbonate, phenyl cellolytic acetate, etc., but not limited to these.
[0257] For example, the solvent is preferably ethylene glycol ether, such as ethylene glycol monoethyl ether, ethylene glycol dimethyl ethyl ether, etc.; ethylene glycol alkyl ether acetate, such as ethyl cellosolve acetate, etc.; ester, such as 2-hydroxyethyl propionate, etc.; carbitol, such as diethylene glycol monomethyl ether, etc.; propylene glycol alkyl ether acetate, such as propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, etc.; alcohol, such as ethanol, etc., or combinations thereof.
[0258] For example, the solvent may be a polar solvent, including propylene glycol monomethyl ether acetate, dipropylene glycol methyl ether acetate, ethanol, ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, 2-butoxyethanol, N-methylpyrrolidone, N-ethylpyrrolidone, propylene carbonate, γ-butyrolactone, or combinations thereof.
[0259] The solvent content can be from 40% to 80% by weight, for example, from 45% to 80% by weight, based on the total amount of the curable component. When the solvent is within the range described, the solvent-based curable component has suitable viscosity and therefore exhibits excellent coating properties when applied over large areas via spin coating and slot coating.
[0260] Another embodiment provides a curable composition, such as a cured layer manufactured using the curable composition, a color filter including the cured layer, and a display device including the color filter. Here, the display device may further include a backlight unit (BLU), wherein the backlight unit may consist of three layers of blue light sources and one layer of green light sources, and the green light source may be an organic light-emitting diode (OLED).
[0261] One method of manufacturing a cured layer may include applying the aforementioned curable composition onto a substrate using an inkjet printing method to form a pattern (S1); and curing the pattern (S2).
[0262] (S1) Pattern Formation
[0263] Curable components can be ideally coated onto a substrate in the range of 0.5 to 20 micrometers using inkjet printing. Inkjet printing can form patterns by spraying a single color through each nozzle and thus repeating the spraying multiple times according to the required number of colors, but patterns can also be formed by spraying the required number of colors simultaneously through each inkjet nozzle to reduce the number of processes.
[0264] (S2) Curing
[0265] The obtained pattern is cured to obtain pixels. In this document, the curing method can be either thermal curing or photocuring. Thermal curing can be performed at or above 100°C, ideally in the range of 100°C to 300°C, and more ideally in the range of 160°C to 250°C. Photocuring may involve irradiation with actinic rays, such as ultraviolet light at 190 nm to 450 nm, or even 200 nm to 500 nm. Irradiation is performed using light sources such as mercury lamps, metal halide lamps, or argon lasers with low, high, or ultra-high pressure. X-rays, electron beams, etc., may also be used as needed.
[0266] Other methods for manufacturing a cured layer may include using a curable composition to manufacture the cured layer via a lithographic method.
[0267] (1) Coating and film formation
[0268] Using methods such as spin coating or slit coating, roller coating, screen printing, or coater coating, a curable composition is coated onto a pre-treated substrate to a desired thickness, for example, between 2 and 10 micrometers. The coated substrate is then heated at 70°C to 90°C for 1 to 10 minutes to remove the solvent and form a film.
[0269] (2) Exposure
[0270] After the resulting film is covered with a screen of a predetermined shape, it is irradiated with photochemical rays, such as UV rays of 190 nm to 450 nm, or UV rays of 200 nm to 500 nm, to form the desired pattern. Irradiation can also be performed using light sources such as low-pressure, high-pressure, or ultra-high-pressure mercury lamps, metal halide lamps, argon lasers, etc. X-rays, electron beams, etc., may also be used as needed.
[0271] When using a high-pressure mercury lamp, the exposure process uses, for example, 500 millijoules per square centimeter (mJ / cm²). 2 The light dose can be less than 500 mJ / cm² (using a 365 nm sensor). However, the light dose can vary depending on the type of each component of the curable composition, their combination ratio, and the dry film thickness.
[0272] (3) Development
[0273] After the exposure process, an alkaline aqueous solution is used to develop the exposed film by dissolving and removing unwanted portions other than the exposed areas, thereby forming an image pattern. In other words, when an alkaline developing solution is used for development, it dissolves the unexposed areas and forms the image color filter pattern.
[0274] (4) Post-processing
[0275] The developed image pattern can be cured by heating or irradiation with photochemical rays to achieve excellent quality in terms of heat resistance, light resistance, contact properties, crack resistance, chemical resistance, high strength, and storage stability.
[0276] Invention Embodiments
[0277] The invention is illustrated in more detail below with reference to examples. However, these examples are not to be construed as limiting the scope of the invention in any way.
[0278] (Preparation of surface-modified quantum dots)
[0279] Preparation Example 1
[0280] (1) Synthesis of the compound represented by the chemical formula Q (first surface modifier):
[0281] 100 g of PH-4 (Hannong Chemicals Inc.) was added to a two-necked round-bottom flask and dissolved thoroughly in 300 mL of tetrahydrofuran (THF). Then, 15.4 g of NaOH and 100 mL of water were added at 0 °C, and the solution was dissolved thoroughly until a clear solution was obtained. A solution prepared by dissolving 73 g of p-toluenesulfonyl chloride in 100 mL of THF was slowly injected into the solution at 0 °C. The injection was carried out for 1 hour, and then the mixture was stirred at room temperature for 12 hours. When the reaction was complete, excess dichloromethane was added and stirred, and a saturated solution of NaHCO3 was added for extraction, titration, and dehydration. After removing the solvent, the residue was dried in a drying oven for 24 hours. 50 g of the dried product was added to a two-necked round-bottom flask and stirred thoroughly in 300 mL of ethanol. Subsequently, 27 g of thiourea was added and dispersed, and the mixture was refluxed at 80 °C for 12 hours. Then, an aqueous solution prepared by dissolving 4.4 g of NaOH in 20 mL of water was injected, and the mixture was stirred for 5 hours. An excess of dichloromethane was added and stirred again, followed by the addition of an aqueous hydrochloric acid solution. Extraction, titration, dehydration, and solvent removal were then performed sequentially. The mixture was then dried in a vacuum oven for 24 hours to obtain the compound represented by the chemical formula Q.
[0282] (2) Synthesis of quantum dots with surface modification using the first and second surface modification materials:
[0283] 0.53 g of compound Q (first surface modifier) and 0.26 g of compound R (second surface modifier; Zn-wedge) were added to 10 g of cyclohexylacetate (CHA) dispersion (InP / ZnSe / ZnS, Hansol Chemical; quantum dot solid content 23 wt%) containing green quantum dots, and stirred for 5 minutes. The mixture was then heated to 80°C and refluxed for 10 hours. After cooling to room temperature, precipitation and centrifugation were performed in cyclohexane to obtain surface-modified quantum dot particles, which were then dried in a vacuum oven for 24 hours to obtain the final particles. (The weight ratio of the first surface modifier to the second surface modifier was 67:33.)
[0284] [Chemical Formula Q]
[0285]
[0286] [Chemical formula R]
[0287]
[0288] Preparation Example 2
[0289] The synthesis method of quantum dots with surface modification using the first and second surface modification materials is the same as that in Preparation Example 1, except that Al is used instead of Zn as the metal atom of the second surface modification material represented by the chemical formula R.
[0290] Preparation Example 3
[0291] The weight ratio of the first surface modifier to the second surface modifier was set to 70:30, while all other aspects were the same as in Preparation Example 1.
[0292] Preparation Example 4
[0293] The weight ratio of the first surface modifier and the second surface modifier was set to 60:40, and everything else was the same as in Preparation Example 1.
[0294] Preparation Example 5
[0295] The weight ratio of the first surface modifier and the second surface modifier was set to 50:50, while everything else was the same as in Preparation Example 1.
[0296] Preparation Example 6
[0297] The weight ratio of the first surface modifier to the second surface modifier was set to 40:60, while all other aspects were the same as in Preparation Example 1.
[0298] Comparative Preparation Example 1
[0299] Quantum dots with surface modification performed using only the first surface modification material represented by the chemical formula Q were synthesized in the same manner as in Preparation Example 1.
[0300] Comparative preparation example 2
[0301] Quantum dots with surface modification by a second surface modifier material represented only by chemical formula R were synthesized in the same manner as in Preparation Example 1.
[0302] Comparative preparation example 3
[0303] Quantum dots with surface modification by a second surface modifier represented only by chemical formula R were synthesized in the same manner as in Preparation Example 1, except that a compound represented by chemical formula S was used instead of the first surface modifier represented by chemical formula Q.
[0304] [Chemical formula S]
[0305]
[0306] Synthesis of compounds represented by the chemical formula S:
[0307] 10 g of PH-4 (Hanong Chemical Co., Ltd.) was added to a two-necked round-bottom flask and dissolved completely in 50 mL of acetone. Then, 4.15 mL of Jones' reagent (2 mol CrO3 aqueous H2SO4, Sigma Aldrich Co., Ltd.) was slowly added dropwise at 0 °C. When the addition was complete, the mixture was stirred at room temperature for 12 hours. When the reaction was complete, excess dichloromethane was added and stirring continued, followed by the addition of a saturated NaHCO3 solution, followed by extraction, titration, and dehydration. The resulting product was dried in a vacuum oven for 24 hours to obtain the compound represented by the chemical formula S.
[0308] (Preparation of curable components)
[0309] Curable compositions according to Examples 1 to 6 and Comparative Examples 1 to 3 were prepared based on the following components.
[0310] (A) Quantum dots
[0311] (A-1) Surface-modified green quantum dots prepared in Example 1
[0312] (A-2) Surface-modified green quantum dots prepared in Example 2
[0313] (A-3) Surface-modified green quantum dots prepared in Example 3
[0314] (A-4) Surface-modified green quantum dots prepared in Example 4
[0315] (A-5) Surface-modified green quantum dots prepared in Example 5
[0316] (A-6) Surface-modified green quantum dots prepared in Example 6
[0317] (A-7) Comparison of surface-modified green quantum dots prepared in Preparation Example 1
[0318] (A-8) Comparison of surface-modified green quantum dots prepared in Preparation Example 2
[0319] (A-9) Comparison of surface-modified green quantum dots prepared in Preparation Example 3
[0320] (B) Polymerizable compounds
[0321] The compound represented by chemical formula 3-2 (M200, Miwon Chemical)
[0322] [Chemical Formula 3-2]
[0323]
[0324] (C) Photopolymerization initiator
[0325] TPO-L (Polynetron)
[0326] (D) Light diffusing agent
[0327] Titanium dioxide dispersion (rutile TiO2; D50 180 nm, solids content 50% by weight, Iridos Co., Ltd.)
[0328] (E) Polymerization inhibitor
[0329] Methylhydroquinone (Tokyo Chemical Co., Ltd.)
[0330] Examples 1 to 6 and Comparative Examples 1 to 3
[0331] Specifically, surface-modified green quantum dots were mixed with a polymerizable compound and stirred for 12 hours. Then, a polymerization inhibitor was added, followed by stirring for 5 minutes. After adding a photopolymerization initiator, a light diffusing agent was added.
[0332] (Taking Example 1 as an example, 41 grams of surface-modified green quantum dots were mixed with 41 grams of a polymerizable compound represented by chemical formula 3-2, and then stirred to prepare a green quantum dot dispersion. 10.95 grams of another curable monomer represented by chemical formula 3-2 and 0.05 grams of a polymerization inhibitor were added to this mixture, and the mixture was stirred for 5 minutes. Subsequently, 3 grams of a photopolymerization initiator and 4 grams of a light diffusing agent were added to this mixture, and the mixture was stirred again to prepare a curable composition (ink).)
[0333] The specific components are shown in Table 1.
[0334] [Table 1]
[0335] (Unit: weight %)
[0336]
[0337] Evaluation: Optical property assessment of curable components
[0338] Each curable component of Examples 1 to 6 and Comparative Examples 1 to 3 was evaluated for its transmittance, frontal brightness, light retention, and lightfastness reliability. The results are shown in Table 2 and... Figure 3 and Figure 4 As shown.
[0339] Specifically, 2 ml of each curable component was spin-coated onto a glass substrate and then exposed at 5 joules for 9 seconds in a nitrogen UV illuminator to form a QD film (9 μm). The external quantum efficiency (EQE) and transmittance at 530 nm were measured using a light efficiency meter (QE-2100, Otsuka Electronics Co., Ltd.). The front brightness of the film was measured using a CS-2000 (Konica Minolta Sensing Co., Ltd.). Light maintenance refers to the relative percentage of the EQE after 24 and 48 hours of exposure, with the initial EQE considered as 100%. This was determined by measuring the initial EQE, the EQE after 24 hours of exposure, and the EQE after 48 hours of exposure. Lightfastness reliability was assessed by measuring the initial external quantum efficiency, then placing the sample (QD film) under a blue LED light source and measuring the external quantum efficiency of the same sample over time.
[0340] [Table 2]
[0341]
[0342] Referring to Table 2, compared to the curable compositions of Comparative Examples 1 to 3, the curable compositions of Examples 1 to 6 exhibited significantly improved frontal brightness by increasing the transmittance at 530 nm without reducing the external quantum efficiency. Furthermore, referring to... Figure 3 and Figure 4 The cured layer (QD film) formed using the curable composition according to the embodiments exhibits superior film properties compared to the cured layer (QD film) formed using the curable composition according to Comparative Example 1, thereby improving optical properties. Furthermore, it can be confirmed from Examples 3 to 5 that by controlling the weight ratio of the first surface modifier and the second surface modifier, the effect of improving light retention rate and lightfastness reliability can be maximized.
[0343] Although the invention has been described in conjunction with what are now considered practical examples, it should be understood that the invention is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent configurations contained within the spirit and scope of the claims. Therefore, the foregoing embodiments should be understood as illustrative and not in any way limiting the invention.
Claims
1. A curable composition, comprising (A) A quantum dot, comprising a first functional group represented by chemical formula 1 and a second functional group represented by chemical formula 2; and (B) Polymerizable compounds: [Chemical Formula 1] [Chemical Formula 2] in, In chemical formula 1 and chemical formula 2, R 1 It is a substituted or unsubstituted C1 to C20 alkyl or a substituted or unsubstituted C6 to C20 aryl. R 2 For substituted or unsubstituted vinyl, L 1 and L 2 Each is independently an ether group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group. L 3 and L 4 Each is independently a substituted or unsubstituted C1 to C20 alkylene or a substituted or unsubstituted C6 to C20 arylene. L 5 It is an ether group, an ester group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group. M is a divalent to tetravalent metal atom. n is an integer from 1 to 10, and m is an integer from 2 to 4.
2. A curable composition, comprising (A) Quantum dots, surface-modified by a first surface-modifying material represented by chemical formula 11 and a second surface-modifying material represented by chemical formula 12; and (B) Polymerizable compounds: [Chemical Formula 11] [Chemical Formula 12] in, In chemical formulas 11 and 12, R 1 It is a substituted or unsubstituted C1 to C20 alkyl or a substituted or unsubstituted C6 to C20 aryl. R 2 For substituted or unsubstituted vinyl, L 1 and L 2 Each is independently an ether group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group. L 3 and L 4 Each is independently a substituted or unsubstituted C1 to C20 alkylene or a substituted or unsubstituted C6 to C20 arylene. L 5 It is an ether group, an ester group, a substituted or unsubstituted C1 to C20 alkylene group, or a substituted or unsubstituted C6 to C20 arylene group. M is a divalent to tetravalent metal atom. n is an integer from 1 to 10, and m is an integer from 2 to 4.
3. The curable composition according to claim 1 or 2, wherein L 1 and L 3 Each is independently a substituted or unsubstituted C1 to C20 alkylene group, and L 2 It is an ether group.
4. The curable composition according to claim 1 or 2, wherein L 4 It is a substituted or unsubstituted C1 to C20 alkylene group.
5. The curable composition according to claim 1 or 2, wherein L 5 It is an ester group.
6. The curable composition according to claim 1, wherein The amount of the first functional group is greater than the amount of the second functional group.
7. The curable composition according to claim 6, wherein The weight of the first functional group is 1 to 3 times the weight of the second functional group.
8. The curable composition according to claim 2, wherein The quantum dots are surface modified when the surface modification mass of the first surface modification material is greater than that of the second surface modification material.
9. The curable composition according to claim 8, wherein The quantum dots are surface modified such that the weight of the first surface modifier on the quantum dots is 1 to 3 times the weight of the second surface modifier.
10. The curable composition according to claim 1 or 2, wherein The polymerizable compounds include those represented by the following chemical formula 3: [Chemical Formula 3] in, In chemical formula 3, L 6 It is a substituted or unsubstituted C1 to C10 alkylene group, a substituted or unsubstituted C3 to C20 cycloalkylene group, or an ether group. -O- ), L 7 and L 8 Each is independently a single-bonded or substituted or unsubstituted C1 to C10 alkylene group, and R 3 and R 4 Each is independently a hydrogen atom or a substituted or unsubstituted C1 to C20 alkyl group.
11. The curable composition according to claim 1 or 2, wherein The curable component has a viscosity of 15 centipoise to 30 centipoise.
12. The curable composition according to claim 1 or 2, wherein The curable component is a solvent-free curable component.
13. The solvent-free curable composition according to claim 12, wherein... Based on the total amount of the solvent-free curable components, the solvent-free curable components include, 5% to 60% by weight of the quantum dots; and 40% to 95% by weight of the polymerizable compound.
14. The curable composition according to claim 1 or 2, wherein The quantum dots include non-cadmium luminescent materials.
15. The curable composition according to claim 14, wherein The quantum dots have a core / shell structure of InP / ZnS or a core / first shell / second shell structure of InP / ZnSe / ZnS.
16. The curable composition according to claim 1 or 2, wherein The quantum dot comprises a core containing Ag, In, Ga, and S; and a shell containing at least two of the elements selected from the group consisting of Ag, Ga, Zn, and S.
17. A curable layer manufactured using the curable composition as described in claim 1 or 2.
18. A color filter comprising the cured layer as described in claim 17.
19. A display device comprising the color filter as claimed in claim 18.
20. The display device according to claim 19, wherein The display device also includes a backlight unit (BLU), and The backlight unit consists of three layers of blue light sources and one layer of green light sources, and The green light source mentioned above is an organic light-emitting diode (OLED).